(untitled) (Journal of Human Sciences, 2025)
This research deals with the history of the founding of the United Nations and its goals related to sustainable development, and sheds light on Libya’s independence, the founding phase of the United Nations Development Program and the projects it implements in local communities. The research focused in particular on the program’s role in preserving the artistic heritage by properly employing funding sources to maintain historical buildings with an architectural heritage. This aims to strengthen the Libyan identity through prior study of the architectural details of “Hosh Al-Kikhia” in the city of Benghazi, preserving its original identity and transforming it into a cultural center after renovation. This approach is considered a qualitative leap in artistic activity that was affected by neglect during the years of conflict in the city of Benghazi. The program continues its role in providing interest in the arts at the local and international levels, and the results of this are evident in the cultural and artistic events that are held in Al-Kikhiya House. Positive effects of this role were observed, including motivating artists to innovate and create and providing visitors with an educational and entertaining experience at the same time.